Agronomic Improvement of Argomulyo Soybean Variety [Glycine max (l) merr] through Induced Mutation by Gamma Irradiation in M1 and M2 Generation - Diana Sofia Hanafiah; Trikoesoemaningtyas Trikoesoemaningtyas; Sudirman Yahya; Desta Wirnas (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2010)
Gamma ray irradiation, especially applied at low doses, is one of methods to produce plant genetic diversity by means of micromutation. The objectives of this research was to determine the radiosensitivity of Argomulyo variety of soybeans (Glycine max (L) Merr) by gamma ray irradiation and to estimate genetic variablity of the crop after  irradiation. To determine the radiosensitivy, the seeds of Argomulyo variety were treated with gamma ray irradiation at  200 Gy, 400 Gy, 600 Gy, 800 Gy, and 1000 Gy. Curve-fit analysis was employed to find the Lethal Doses 50 (LD50) value . To evaluate the genetic variablity after irradiation with gamma ray, seeds of Argomulyo was irradiated under LD50  at doses of 0 Gy, 50 Gy, 100 Gy, 150 Gy, and 200 Gy.  The results showed that LD50 value was 457.17 Gy. The study found that for Argomulyo variety the LD20 was 490.93 Gy and the LD50 was 457.17 Gy.  Genetic variability was observed in various agronomic characters of M2 generation after low dose of gamma ray irradiation treatment of 50, 100, 150 and 200 Gy. The highest genetic variability was found at 200 Gy for plant height, number of productive nodes, and number of pods.  The variability of agronomic characters of soybean after irradiation was due to genetic factors. The highest heritability estimates was observed in plant height and number of productive pods. The succeding generation of putative mutants will be selected for productivity and drought tolerance.